Antara Disiplin dan Kriminalisasi Guru: Tinjauan Teologis Pastoral atas Krisis Otoritas dalam Pendidikan - Simanjuntak, Helmina; Sihombing, Roida; Yuswanto, Felisitas (STP St. Bonaventura Medan, 2026)
The criminalization of teachers in the context of student discipline reveals a profound crisis of authority within contemporary education. This article aims to examine the tension between pedagogical discipline and legal mechanisms through a theological-pastoral perspective. Employing a qualitative approach grounded in critical pastoral theology, the study integrates empirical data from international institutional reports and educational policy analyses with normative theological reflection rooted in Scripture and Church teachings. The discussion demonstrates that the weakening legitimacy of teacher authority, the growing climate of fear due to legal prosecution, and the disintegration of shared responsibility between schools and parents contribute significantly to the erosion of character education and the rise of aggressive student behavior. From a Christian theological perspective, discipline is understood as a pedagogical act grounded in moral responsibility and service rather than as an expression of violence. This article argues that the crisis of authority in education is both structural and pastoral, requiring active engagement from the Church to restore healthy relationships among educators, parents, and students. Contextual theological-pastoral reflection is proposed as a meaningful contribution to the renewal of educational practice and the strengthening of character formation amid contemporary social and legal challenges.